Convective Solvent Transport Pathways for Absorption of Drugs from Topical Formulation - Abhijeet Maurya; Jungeun Bae; Vanaja Kenchappa; H. N. Shivakumar; Howard Maibach; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2022)

Development and Validation of HPLC Method for Efinaconazole: Application to Human Nail Permeation Studies - Praveen Kolimi; Vijay Kumar Shankar; Abhishek Shettar; Srinath Rangappa; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2022)

Chemotherapeutic Agent-Induced Vulvodynia, an Experimental Model - Srinath Rangappa; Vijay Kumar Shankar; Seongbong Jo; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2021)

A One-Step Twin-Screw Melt Granulation with Gelucire 48/16 and Surface Adsorbent to Improve the Solubility of Poorly Soluble Drugs: Effect of Formulation Variables on Dissolution and Stability - Sandeep Sarabu; Venkata Raman Kallakunta; Arun Butreddy; Karthik Yadav Janga; Srinivas Ajjarapu; Suresh Bandari; Feng Zhang; S. Narasimha Murthy; Michael A. Repka (AAPS PharmSciTech, 2021)

A Rapid Tool to Optimize Process Variables for Continuous Manufacturing of Metronidazole Ointment Using Melt Extrusion Technique - Srinivas Ajjarapu; Srinath Rangappa; Vijay Kumar Shankar; Abhishek Shettar; H.N. Shiva Kumar; Vijay I. Kulkarni; Micheal A Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2020)

Stability of Vaccines - N. Dumpa; K. Goel; Yuhan Guo; H. McFall; Amit Raviraj Pillai; Ashay Shukla; M. A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2019)

Interactions Between Biological Products and Product Packaging and Potential Approaches to Overcome Them - Minjia Wang; Yusheng Li; Priyanka Srinivasan; Zhiqing Hu; Rui Wang; Anggrida Saragih; M. A. Repka; S. N. Murthy (AAPS PharmSciTech, 2018)

Micronized Zaleplon Delivery via Orodispersible Film and Orodispersible Tablets - Prashanth Manda; Carmen Popescu; Abhishek Juluri; Karthik Janga; Praneeth Rao Kakulamarri; Sushmitha Narishetty; S. Narasimha Murthy; Michael A. Repka (AAPS PharmSciTech, 2018)

Excipient Stability: a Critical Aspect in Stability of Pharmaceuticals - S. Narasimha Murthy; Michael A. Repka (AAPS PharmSciTech, 2018)

Microbial Stability of Pharmaceutical and Cosmetic Products - Huy Dao; Prit Lakhani; Anitha Police; Venkataraman Kallakunta; Sankar Srinivas Ajjarapu; Kai-Wei Wu; Pranav Ponkshe; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2018)

Photostability Issues in Pharmaceutical Dosage Forms and Photostabilization - Karthik Yadav Janga; Tamara King; Nan Ji; Sandeep Sarabu; Gauri Shadambikar; Sagar Sawant; Pengchong Xu; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2018)

Solid-State Stability Issues of Drugs in Transdermal Patch Formulations - Purnendu Kumar Sharma; Apoorva Panda; Adwait Pradhan; Jiaxiang Zhang; Ruchi Thakkar; Chang-Hee Whang; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2018)

Excipient Stability in Oral Solid Dosage Forms: A Review - Mittal A. Darji; Rahul M. Lalge; Sushrut P. Marathe; Tarul D. Mulay; Tasnim Fatima; Alia Alshammari; Hyung Kyung Lee; Michael A Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2018)

A Novel Apremilast Nail Lacquer Formulation for the Treatment of Nail Psoriasis - Avadhesh Singh Kushwaha; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2017)

Bioadhesive Drug Delivery System for Enhancing the Permeability of a BCS Class III Drug via Hot-Melt Extrusion Technology - Nicole S. Mendonsa; Priyanka Thipsay; Dong Wuk Kim; Scott T. Martin; Michael A. Repka (AAPS PharmSciTech, 2017)

Ocular Disposition of ∆8-Tetrahydrocannabinol from Various Topical Ophthalmic Formulations - Nagendra S. Punyamurthula; Goutham R. Adelli; Waseem Gul; Michael A. Repka; Mahmoud A. ElSohly; Soumyajit Majumdar (AAPS PharmSciTech, 2017)

Development of an Ointment Formulation Using Hot-Melt Extrusion Technology - Ajinkya M. Bhagurkar; Muralikrishnan Angamuthu; Hemlata Patil; Roshan V. Tiwari; Abhijeet Maurya; Seyed Meysam Hashemnejad; Santanu Kundu; S. Narasimha Murthy; Michael A. Repka (AAPS PharmSciTech, 2016)

Taste Masking of Griseofulvin and Caffeine Anhydrous Using Kleptose Linecaps DE17 by Hot Melt Extrusion - Abhishek Juluri; Carmen Popescu; Leon Zhou; Reena N. Murthy; Vanaja K. Gowda; Chetan Kumar P; Manjeet B. Pimparade; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2016)

Influence of Process and Formulation Parameters on Dissolution and Stability Characteristics of Kollidon® VA 64 Hot-Melt Extrudates - Sindhuri Maddineni; Sunil Kumar Battu; Joe Morott; Soumyajit Majumdar; S. N. Murthy; Michael A. Repka (AAPS PharmSciTech, 2015)

Microporation and ‘Iron’tophoresis for Treating Iron Deficiency Anemia - Naresh Modepalli; Seongbong Jo; Michael A. Repka; S. Narasimha Murthy (Pharmaceutical Research, 2013)

Klucel™ EF and ELF polymers for immediate-release oral dosage forms prepared by melt extrusion technology - Noorullah Naqvi Mohammed; Soumyajit Majumdar; Abhilasha Singh; Weibin Deng; Narasimha S. Murthy; Elanor Pinto; Divya Tewari; Thomas Durig; Michael A. Repka (AAPS PharmSciTech, 2012)

The supposed lack of trade-off among Daphnia galeata life history traits is explained by increased adult mortality in Chaoborus conditioned treatments - A. Weber; S. Vesela; S. Repka (Hydrobiologia, 2003)

Maximum rates of N 2 fixation and primary production are out of phase in a developing cyanobacterial bloom in the Baltic Sea - J. R. Gallon; A. M. Evans; D. A. Jones; P. Albertano; R. Congestri; B. Bergman; K. Gundersen; K. M. Orcutt; K. von Bröckel; P. Fritsche; M. Meyerhöfer; K. Nachtigall; et al. (Limnology and Oceanography, 2002)
Although N 2 ‐fixing cyanobacteria contribute significantly to oceanic sequestration of atmospheric CO 2 , little is known about how N 2 fixation and carbon fixation (primary production) interact in natural populations of marine cyanobacteria. In a developing cyanobacterial bloom in the Baltic Sea, rates of N 2 fixation (acetylene reduction) showed both diurnal and longer‐term fluctuations. The latter reflected fluctuations in the nitrogen status of the cyanobacterial population and could be correlated with variations in the ratio of acetylene reduced to 15 N 2 assimilated. The value of this ratio may provide useful information about the release of newly fixed nitrogen by a cyanobacterial population. However, although the diurnal fluctuations in N 2 fixation broadly paralleled diurnal fluctuations in carbon fixation, the longer‐term fluctuations in these two processes were out of phase.

Effects of dissolved cyanobacterial toxins on the survival and egg hatching of estuarine calanoid copepods - Reinikainen M.; Lindvall F.; Meriluoto J.; Repka S.; Sivonen K.; Spoof L.; Wahlsten M. (Marine Biology, 2002)